2021
DOI: 10.5500/wjt.v11.i7.254
|View full text |Cite
|
Sign up to set email alerts
|

Chances and risks of sodium-glucose cotransporter 2 inhibitors in solid organ transplantation: A review of literatures

Abstract: Solid organ transplantation offers life-saving treatment for patients with end-organ dysfunction. Patient survival and quality of life have improved over the past few decades as a result of pharmacological development, expansion of the donor pool, technological advances and standardization of practices related to transplantation. Still, transplantation is associated with cardiovascular complications, of which post-transplant diabetes mellitus (PTDM) is one of the most important. PTDM increases mortality, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…In the CANVAS research, participants who were randomly assigned to the canagliflozin group experienced a lower incidence of cardiovascular events. The study also revealed that canagliflozin-assigned subjects were less likely to have end-stage renal disease, a decline in eGFR, or albuminuria progression [11].…”
Section: Table 3: Mechanism Of Action Of Immunosuppressive Drugsmentioning
confidence: 85%
See 2 more Smart Citations
“…In the CANVAS research, participants who were randomly assigned to the canagliflozin group experienced a lower incidence of cardiovascular events. The study also revealed that canagliflozin-assigned subjects were less likely to have end-stage renal disease, a decline in eGFR, or albuminuria progression [11].…”
Section: Table 3: Mechanism Of Action Of Immunosuppressive Drugsmentioning
confidence: 85%
“…In the CANVAS research, participants who were randomly assigned to the canagliflozin group experienced a lower incidence of cardiovascular events. The study also revealed that canagliflozin-assigned subjects were less likely to have end-stage renal disease, a decline in eGFR, or albuminuria progression [ 11 ]. According to an RCT trial results, individuals with bilateral nephrectomies showed decreased de novo glucose production for increased glucose loss caused by SGLT2 inhibitors indicating that the hepatic renal axis is deranged due to lack of efferent nerve stimulation [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the benefits published in these studies are also aligned with those demonstrated in the general population [ 77 , 78 , 79 , 80 ]. Nevertheless, the most frequently observed side effects are precisely effects that could be potentially harmful to this population profile, such as severe or recurrent urinary tract infections and impaired kidney function [ 81 , 82 ]. Table 3 and Table 4 summarize the effects observed in the studies conducted to date.…”
Section: New Antidiabetics In Renal Transplant Sglt2 Inhibitorsmentioning
confidence: 99%
“…Acute renal failure could be another disadvantage of these drugs, which in some cases forces their withdrawal and in others could delay or discourage their initiation [ 92 ]. Some studies have shown unchanging renal function despite the onset of SGLT2i, [ 81 , 84 , 86 , 87 , 89 , 90 ], while other studies showed an early impairment of renal function (eGFR-dippers) (18–14%), but followed by later stabilization [ 85 , 88 , 93 ] or an even slower decline in renal function with respect to the control group [ 94 ].…”
Section: New Antidiabetics In Renal Transplant Sglt2 Inhibitorsmentioning
confidence: 99%